A new ISO 9001 diffusion index - Sampaio, Paulo (2013)
Purpose – ISO 9001 certification is nowadays considered to be one of the most effective tools that can be adopted for guiding the management of Quality Systems. The stunning growth observed by these standards all over the world confirms a strong polarization of enterprises’ interest in this practice. Owing to the wide incidence of this phenomenon, a deep investigation of ISO 9001 diffusion over time is of mandatory importance. In the line of our previous publications, this paper derives from a research project that we are conducting in Portugal in order to develop the “ISO 9001 European Scoreboard”, aimed at studying and ranking European Union countries based on quality management systems diffusion. Methodology/Approach – In order to achieve such a goal, the authors have performed a set of statistical analyses over public data sets. Findings – Based on the model developed and in the analyses performed we were able to find out clusters of countries with different ISO 9001 evolution stages, derived from the ISO 9001 per 1000 inhabitants’ scores and countries growth indexes. Originality – With this scoreboard we are able to categorize and rank countries based on the quality management systems evolution (growth rates) over the past few years. In the end, such an “ISO 9001 European Scoreboard” will be an instrument to provide a comparative assessment of quality management practices over the European Union states, leading to the dynamic evaluation of their “macroquality” levels achieved, according to such a standard. We believe that such results provide an additional important contribution to the study of management systems diffusion/evolution, aimed at providing more fact-based insights and understandings.